Efficient Non‐Doped Blue Electro‐fluorescence with Boosted and Balanced Carrier Mobilities. (7th March 2022) - Wang, Runze; Li, Tengyue; Liu, Chaoke; Xie, Mingliang; Zhou, Huayi; Sun, Qikun; Yang, Bing; Zhang, Shi‐Tong; Xue, Shanfeng; Yang, Wenjun
Abstract: One of the most important issues of the organic light‐emitting diode (OLED) is the highly efficient blue‐emissive material, which demands both excellent photoluminescent quantum yield (PLQY) and balanced carrier mobilities. Herein, a series of blue‐emissive donor–π–acceptor (D–π–A) materials with fluorene π‐bridge and their D–A analogues are synthesized and discovered with a theoretical combined experimental method. Based on the excellent electron mobility of the oxadiazole (OXZ) acceptor, it is further proven that the insertion of the fluorene π‐bridge can not only contribute to the formation of hybrid local and charge‐transfer excited state with high PLQY, but also give rise to the hole mobilities by enhanced intermolecular face‐to‐face stacking. As a result, the non‐doped OLED of TPACFOXZ exhibits a high maximum external quantum efficiency approaching 10% with boosted and balanced hole and electron mobilities of 5.60 × 10 −5 and 6.60 × 10 −5 cm 2 V −1 s −1, respectively, which are among the best results of the non‐doped blue fluorescent OLEDs. Abstract : Incorporation of fluorene‐bridge in donor–acceptor (D–A) molecules is proven to demonstrates double functions: high photoluminescent quantum yield and balanced carrier mobilities due to decent stacking patterns. Remarkably, the non‐doped OLED of the fluorene‐bridged D–A materials demonstrate excellent electroluminescent performances with high efficiency, low driving voltage, low rolling‐off with boosted and balanced carrier mobility.